2014
DOI: 10.1017/s0029665114001505
|View full text |Cite
|
Sign up to set email alerts
|

Digital and social media opportunities for dietary behaviour change

Abstract: The way that people communicate, consume media and seek and receive information is changing. Forty per cent of the world's population now has an internet connection, the average global social media penetration is 39 % and 1·5 billion people have internet access via mobile phone. This large-scale move in population use of digital, social and mobile media presents an unprecedented opportunity to connect with individuals on issues concerning health. The present paper aims to investigate these opportunities in rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(93 citation statements)
references
References 58 publications
0
83
1
2
Order By: Relevance
“…There is emerging research on adaptation of behavioral interventions for social media delivery [36], and on which behavior change techniques could be applied in digital contexts (eg, goal setting, barrier identification/problem solving, prompt review of behavior goals) [16]; however, these results do not explain how behavior change techniques should be translated into practice applications in online settings (ie, when, where, and in what format they will be effective). Webb et al [12] identified behavior change techniques associated with larger effect sizes in Web-based health interventions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is emerging research on adaptation of behavioral interventions for social media delivery [36], and on which behavior change techniques could be applied in digital contexts (eg, goal setting, barrier identification/problem solving, prompt review of behavior goals) [16]; however, these results do not explain how behavior change techniques should be translated into practice applications in online settings (ie, when, where, and in what format they will be effective). Webb et al [12] identified behavior change techniques associated with larger effect sizes in Web-based health interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Behavior change techniques were grouped by the theoretical domains of the Theoretical Domains Framework [25], based on the structure proposed by Cane et al [35]. Two authors (A-AD and AL) independently chose theory-based methods that were applicable in the context of an online dietary intervention delivered through a blog [16,36]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This high utilization of online resources to seek information about DS presents great opportunities [19,20,21]. The increasing availability and plethora of online information about DS and health, as well as the ubiquity and accessibility of the Internet and SMPs, allows more youth to seek and find information about DS [22].…”
Section: Sources Of Information About Ds: Internet and Smps As Enablersmentioning
confidence: 99%
“…For instance, [39] and [40] warned for the potential harm associated with unsafe social media content, as people seeking health information has to recognize that the authorship is difficult to determine, sources are rarely provided, and users may post their personal opinions in social marketing [41] and cause concerns of inequalities [42], privacy, misinformation and lack of evaluation [43]. For instance, there is a scandal involved China's top internet search engine, Baidu, of which the company's search engine provides medical information based on bidding process that caused the death of a university student [44].…”
Section: Potentials Of Social Media In Health Communicationmentioning
confidence: 99%